Pengembangan Media Ice Breaking Berbasis 4C Pada Pembelajaran Tematik Integratif Peserta Didik Kelas V MIS Nurul Huda Kupang - Kurniawan, Budi; Nuriyah, Nuriyah (Jurnal Penelitian dan Pengembangan Pendidikan, 2020)
This research including development research (Research and Development) aims to Communication, Collaborative, Critical Thinking, and Creativity (4C)-based Ice Breaking Learning Media Developed on Integrative Thematic Learning. The subjects in this study were students and fifth grade teachers of MIS Nurul Huda, Kupang. The development model used in this study is the Four D development model which consists of 4 stages: (1) define, (2) design, (3) develop, and (4) disseminate. This 4C-based Ice Breaking learning media developed media has carried out a trial process consisting of one-on-one trials of 10 people, small group trials of 12 people and class trials of 34 students. The 4C-based Ice Breaking learning media developed have been validated by the Validator and has undergone revisions so that it gets very feasible and practical results to be used in learning because based on the research results of the Guidelines for Making 4C Ice Breaking Media and 4C Ice Breaking LKPD, and all the media in the latest book, including: puzzles, flipcharts, leaflets, sketches, and learning videos meet very valid criteria so they are very feasible and very practical to be used in the learning process.